PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MEDIA GAMBAR PADA SISWA KELAS V SD NEGERI 010 RAMBAH - Pariang Sonang Siregar; Abdul Ginda Putra Hasibuan (STKIP ROKANIA, 2017)
This research is a classroom action research conducted at SD Negeri 010 Rambah with total of 19 students consisting of 5 male students and 14 female students. This classroom action research using image media as an improvement of mathematics learning result of grade V students of SD Negeri 010 Rambah. This research was conducted two cycles. Each cycle consists of planning, execution, observation and evaluation as well as reflection. The material in this research is simple wake-up nets, and fold symmetry. The results obtained in learning mathematics by using the image media increased from the average class 79.26 in the first cycle to 80.53 in cycle II, while the completeness increased from 94.74% in cycle I to 100% in cycle II. This proves that the media is very suitable picture applied in learning mathematics so that student learning outcomes can increase